Mario Trindade's Training Method: The Journey to 100m Wheelchair Gold Medal at European Championships in Berlin (2018) - Eduarda Coelho; Tiago M. Barbosa; Pedro Miguel Forte; Fávia Costa; José Vilaça-Alves (Desafio Singular, 2024)
This article aims to present Paralympic athlete Mario Trindade's training to become the European Champion at the 100-meter wheelchair race in Berlin 2018. The lack of information on this specific training has impaired the beginning of this journey. However, the daily monitoring of this athlete over 20 years has permitted us to realise that the training methods of athletes with disabilities are not very different from those of others. Thus, it is important to understand the different responses to exercise. The degree of improvement after a training program depends on the characteristics of the vertebral-medullary lesion, the training history, and the training ability of the athlete, which is determined by the amount of active muscle mass available. Considering these aspects, we aim to describe the summer training macrocycle that is developed for the 100 m wheelchair race, which is a combined work developed by a multidisciplinary team. We will start by providing a theoretical background on para-athletics events, specifically wheelchair competitions. Afterwards, we will characterise the athlete and discuss his track and strength training, which prepared him to obtain the gold medal in 2018.